Ordinary People, Extraordinary Actions Refuge Through Activism at Ottawa's St. Joe's Parish - Morris, Stéfanie (Politics and Public Policy, 2022)
What motivates "ordinary people" to support refugees emotionally and financially? This is a timely question considering the number of displaced people in today's world is at an all-time high. To help counter this crisis, it is imperative for the Canadian government to determine which policies encourage volunteers to welcome asylum seekers, and which ones must be reviewed. Ordinary People, Extraordinary Actions relates the story of the St. Joseph's Parish Refugee Outreach Committee over its thirty years in action, revealing how seemingly small decisions and actions have led to significant changes in policies and in people's lives-and how they can do so again in the future. By helping readers-young and old, secular and faith-oriented-understand what drives individuals and communities to welcome refugees with open hearts and open arms, the authors hope to inspire people across Canada and beyond its borders to strengthen our collective willingness and ability to offer refuge as a lifesaving protection for those who need it.